2015
DOI: 10.1016/j.rmed.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, placebo-controlled, Phase II, dose-ranging trial of once-daily treatment with olodaterol, a novel long-acting β2-agonist, for 4 weeks in patients with chronic obstructive pulmonary disease

Abstract: ClinicalTrials.gov: NCT00452400.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…This trial was part of a novel approach to dose finding with drug combinations, in which the dose response of each component within the FDC was explored to confirm whether it is the same as the dose response when used as monotherapy. The dose response of olodaterol alone was investigated in olodaterol dose-finding studies, which identified olodaterol 5 and 10 µg as the doses to be taken forward to the phase III trials [ 14 ], and the dose response of tiotropium monotherapy in the Respimat inhaler has been investigated [ 15 ], with 5 µg performing best and subsequently licensed in COPD. The present study was not powered to detect differences between different combined doses of tiotropium + olodaterol, but it was sufficient to identify dose ordering for FEV 1 responses for the dose combinations.…”
Section: Discussionmentioning
confidence: 99%
“…This trial was part of a novel approach to dose finding with drug combinations, in which the dose response of each component within the FDC was explored to confirm whether it is the same as the dose response when used as monotherapy. The dose response of olodaterol alone was investigated in olodaterol dose-finding studies, which identified olodaterol 5 and 10 µg as the doses to be taken forward to the phase III trials [ 14 ], and the dose response of tiotropium monotherapy in the Respimat inhaler has been investigated [ 15 ], with 5 µg performing best and subsequently licensed in COPD. The present study was not powered to detect differences between different combined doses of tiotropium + olodaterol, but it was sufficient to identify dose ordering for FEV 1 responses for the dose combinations.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from this study are broadly similar to another Phase II olodaterol dose-finding study (1222.5; NCT00452400) in non-Japanese patients with COPD, which provided evidence of the bronchodilator efficacy of 2 µg, 5 µg, 10 µg, and 20 µg of olodaterol QD over 24 hours. 10 Regarding the comparison of the systemic exposure of olodaterol, systemic exposure tended to be higher in the current study than in the non-Japanese study (ie, geometric mean C max,ss 5.92 pg/mL versus 4.02 pg/mL [5 µg], 13.1 pg/mL versus 7.13 pg/mL [10 µg], and AUC 0–1,ss 4.85 pg·h/mL versus 3.38 pg·h/mL [5 µg], 10.8 pg·h/mL versus 5.76 pg·h/mL [10 µg]). The main metabolic pathway of olodaterol clearance is related to uridine 5′-diphospho-g lucuronosyltransferase (UGT), for which racial difference in activity has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to efficacy, in the study with non-Japanese patients, the change from baseline in trough FEV 1 was 0.046, 0.082, and 0.109 with 2 µg, 5 µg, and 10 µg of olodaterol. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olodaterol exerts an efficacious, 24-hour-lasting protection against experimental ACh-induced bronchoconstriction in both guinea pigs and dogs. 38 Used by COPD patients once daily at dosages ranging from 2 to 20 µg, olodaterol elicits dose-dependent, significant increases in FEV 1 40 , 41 Two replicate, randomized, double-blind, placebo-controlled, and parallel-group phase III studies, carried out in patients with moderate to very severe COPD, have shown that olodaterol 5 and 10 µg significantly enhanced trough FEV 1 , and this bronchodilation was associated with an incidence of adverse events (AEs) comparable to that caused by placebo. 42 Such findings were further corroborated by other two replicate, multicenter studies, which also demonstrated that the improvements in lung function produced by olodaterol translated into symptomatic benefits for COPD patients.…”
Section: Mechanism Of Action and Therapeutic Profile Of Olodaterolmentioning
confidence: 99%